Cancers of the corpus uteri treated in South Australian public hospitals: Trends in clinical management and survival across three decades. (8th July 2020) - Roder, David; Selva‐Nayagam, Sudarsha; Paramasivam, Sellvakumaran; Keefe, Dorothy; Olver, Ian; Miller, Caroline; Buckley, Elizabeth; Powell, Kate; Fusco, Kellie; Buranyi‐Trevarton, Dianne; Oehler, Martin
Abstract: Objective: To investigate treatment and survival over three decades. Methods: Clinical registry data from three major public hospitals analysed using Kaplan–Meier product‐limit estimates and multivariate proportional hazard regression to determine disease‐specific survival. Results: Five‐year survival increased from 75% to 84%. The adjusted hazard ratio (HR, 95% CI) was 0.56 (0.41, 0.77) for 2010–2016 compared with 1984–1989 and was higher for: ages 80+ years; more advanced stages; poorly differentiated tumours; and complex mixed epithelial and mesenchymal tumours and sarcomas. Treatment was by surgery (92%), radiotherapy (33%), chemotherapy (12%) and hormone therapy (10%). Adjusted analyses showed radiotherapy and hormone therapy were less common from 1990 and chemotherapy more common for 2010–2016. Treatment likelihood was lower for ages ≥80 years, mixed epithelial and mesenchymal tumours receiving surgery and chemotherapy, but higher for radiotherapy. Advanced cancers (FIGO stage IV) had less surgery but more non‐surgical treatments. Marginal evidence presented of more hormone therapy for high socio‐economic areas. Conclusions: Survival was equivalent to national figures for Australia and the United States, but potentially higher than for England and Wales. Cases aged 80+ years had less care and poorer survival. Findings illustrate the complementary roles of hospital and population‐based registries in local service evaluation.